End of life care over four decades in a quaternary neonatal intensive care unit - Barry, A; Prentice, T; Wilkinson, D (Wiley, 2022)
Background: Death in the neonatal intensive care unit commonly follows a decision to withdraw or limit life-sustaining treatment. Advances in medicine has changed the nature of life-sustaining interventions available and the potential prognosis for many newborn conditions.